San Felipe de Jesús o las Capuchinas: un convento olvidado - Alejandro Tonatiuh Romero Contreras (Ciencia Ergo Sum)
In the ancient Mexico city existed a little poor nun convent between La Celada and Acequia Real streets (now called Venustiano Carranza and 16 de Septiembre, respectively). Due to its total disappearance and the few documents about it, this convent is perhaps the less studied of all those that existed in the colonys capital. This paper shows a part of the social history of the Capuchin order, as well as the architectonic and artistic evolution of this colonial jewel. Data was obtained from the colonys archives and some other written sources (from the XVII c. until its disappearance in the second part of the XIX c.). The high price of the land is considered the cause of the convents demolition.